Effect of quercetin supplementation on serum uric acid in obese male patients - Pathomweepisut, Natlada; Thetsana, Paphitchaya; Tengumnuay, Patana (Journal of Medicine and Health Sciences, 2022)
Abstract Hyperuricemia can lead to gouty arthritis and kidney stones and is also associated with cardiovascular disease. However, the treatment guidelines have not suggested ways to lower uric acid agents in healthy people. Therefore, various phytochemicals are used to replace them, such as quercetin, which inhibits the xanthine oxidase enzyme and to enhance the excretion of uric acid through the kidneys. Therefore, the objective of this study was to study the effect of quercetin on serum uric acid levels in obese male patients. The randomized, double blinded, controlled trial was conducted with 43 obese male patients, aged between 25-60 years old, and with a baseline serum uric acid level higher than 5.2 mg/dl. The serum uric acid level was measured before and after four weeks of taking a 500 mg/day quercetin supplement. The adverse effects of kidney and liver function were monitored by serum creatinine, aspartate aminotransferase and alanine aminotransferase. The results found that after four weeks, the serum uric acid levels were significantly reduced by 0.05 mg/dl (p-value 0.012, 95%CI = -0.88, -0.12) without any adverse effects on kidney and liver function. In conclusion, quercetin is vital in terms of reducing serum uric acid levels and preventing the diseases associated with hyperuricemia.